Are farmer organizations effective intermediaries and facilitators of agricultural innovations processes? Evidence from Tunisia - Ouerghemmi, Hassen; Frija, Aymen; Souissi, Asma; Carpentier, Irène; Shiri, Zahra; Dhehibi, Boubaker; Rejeb, Hichem (Frontiers in Sustainable Food Systems, 2024)
Integration of productivity, resource management, and institutional innovations is crucial across different system levels. Traditional research and extension services face challenges in disseminating innovations effectively, leading to the emergence of agricultural innovation system (AIS) approach. AIS involves collaboration among various stakeholders to improve technological, managerial, and institutional aspects in agriculture. Intermediary actors play a pivotal role in facilitating innovation exchange and learning processes. In Tunisia, farmer organizations (FOs) like agricultural development groups (GDAs) and mutual companies for agricultural services (SMSAs) are key intermediaries. However, there is a lack of comprehensive assessments of FOs' innovation roles, which this study aims to address using Social Network Analysis (SNA) method. The findings aim to shed light on FOs' effectiveness as innovation intermediaries and identify potential challenges and benefits associated with their roles in innovation processes through the comparison of three farmers groups divided by their membership status to detect the effect of FO presence or absence on innovation facilitation and actor's configuration. The studied sample involves 592 farmers from Kef and Siliana governorates in northwestern Tunisia. The results show that farmer organizations (FOs) are playing a crucial role in facilitating collaboration and knowledge exchange among farmers and other agricultural actors. However, their effectiveness varies depending on membership status and stays always contextually influenced. While FOs contribute to reshaping sales channels and optimizing access to services, they face limitations in promoting inclusivity and equitable knowledge sharing. The recommendations include strengthening FOs' social dimension, addressing trust barriers, and investing in reinforcement measures especially in human capital to enhance their functionality. Strengthening measures can take many forms, such as facilitating regulation and investing in capacity building. Long-term strategies should re-evaluate the effectiveness of collective action and focus on fostering a culture of shared learning and local empowerment.